2012
DOI: 10.3928/01477447-20120621-13
|View full text |Cite
|
Sign up to set email alerts
|

Extensively Porous-coated Stems for Femoral Revision: Reliable Choice for Stem Revision in Paprosky Femoral Type III Defects

Abstract: Between January 1999 and August 2008, ninety-six femoral revisions were performed with extensively porous-coated stems in Paprosky type III femoral defects (89 type IIIA and 7 type IIIB defects). Seven type IIIB defects with a mean canal of 16.5 mm were observed; 6 defects achieved stable bone ingrowth and 1 achieved stable fibrous condition. Average postoperative Harris Hip Score was 92.3±8 (range, 77-100), and all scores improved postoperatively. At a mean follow-up of 65.7 months, 92 stems achieved bone ing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
1
19
0
1
Order By: Relevance
“…Based on clinical studies by Paprosky et al [22,23], use of an extensively porous coated stem when at least 4 cm of intact diaphyseal bone was present was associated with excellent survivorship (95% survivorship; mean followup, 13.2 years). Other authors [5,21] have reported similar results. Conversely, 21% of patients experienced stem loosening if diaphyseal fixation was less than 4 cm [23].…”
Section: Descriptionsupporting
confidence: 75%
“…Based on clinical studies by Paprosky et al [22,23], use of an extensively porous coated stem when at least 4 cm of intact diaphyseal bone was present was associated with excellent survivorship (95% survivorship; mean followup, 13.2 years). Other authors [5,21] have reported similar results. Conversely, 21% of patients experienced stem loosening if diaphyseal fixation was less than 4 cm [23].…”
Section: Descriptionsupporting
confidence: 75%
“…Cylindrical fully-porous coated femoral stems have been shown to be another valuable option for revision THA in the setting of proximal femoral bone loss [10,[22][23][24]. Reports on the use of this stem design have shown reliable ingrowth, however thigh pain and stress shielding are potential concerns when using this style of femoral stem [10,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the use of this stem design have shown reliable ingrowth, however thigh pain and stress shielding are potential concerns when using this style of femoral stem [10,[22][23][24]. Likewise many authors recommend against using this type of stem in the setting of Paprosky IIIb and IV femoral deficiency [10,[22][23][24].…”
Section: Discussionmentioning
confidence: 99%
“…These defects are typically reconstructed using an extensively porous coated stem or a modular tapered stem. Chung and colleagues 35 …”
Section: Make An Incision Distally For Insertion Of a Distalmentioning
confidence: 99%